Kajian Silika Tanah pada Berbagai Pengunaan Lahan di Kecamatan Madiun. Study Of Soil silica On Various Land Uses in madiun Sub-Distric : pertanian, ilmu tanah, silika - Primadi Hindun Labiba; Punomo Edi Sasongko; Siswanto (BPFP Universitas Bengkulu, 2025)
[RELATIONSHIP BETWEEN SOIL SILICA AND PLANT TISSUE SILICA ACROSS DIFFERENT LAND USES IN MADIUN DISTRIC]. Agricultural land in Madiun District frequently experiences drought during the dry season, reducing plant tolerance to environmental stress. Although not an essential nutrient, silica can enhance plant resistance to drought stress and plays a role in nutrient binding. This study aimed to examine soil and plant tissue silica content across various land uses in Madiun District. The research was conducted on three land use units in Gunungsari, Banjarsari, and Sirapan Villages. Soil and plant samples were collected at 0–30 cm and 30–60 cm depths. Soil analyses included physical properties (texture and moisture content) and chemical properties (pH,organic C, total N, cation exchange capacity, and silica content). Data were analyzed using correlation and linear regression tests. Results showed that the highest silica content in plant tissue was found in paddy fields (40%) and the lowest in sugarcane fields (29%). Soil silica content in sugarcane fields was highest in Banjarsari Village (57.31%) and lowest in Sirapan Village (56.75%), while in paddy fields it was highest in Gunungsari Village (66.69%) and lowest in Sirapan Village (65.57%). The presence of silica influenced soil cation exchange capacity and nitrogen content, and it contributed to increasing plant tolerance to drought by reducing water loss through transpiration. The study recommends land management practices to enhance silica availability, such as returning crop residues to the soil. Full text pdf